2011
DOI: 10.1007/s10329-011-0254-6
|View full text |Cite
|
Sign up to set email alerts
|

Tool-use to obtain honey by chimpanzees at Bulindi: new record from Uganda

Abstract: Honey-gathering from bee nests has been recorded at chimpanzee (Pan troglodytes) study sites across tropical Africa. Different populations employ different strategies, ranging from simple 'smash-and grab' raids to use of sophisticated tool-sets, i.e., two or more types of tool used sequentially in a single task. In this paper I present evidence of tool-use, and the probable use of a tool-set, for honey-gathering by unhabituated chimpanzees at Bulindi, a forest-farm mosaic south of the Budongo Forest in Uganda.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Although these results still demand further confirmation, they currently suggest that stick use is absent throughout Budongo Forest. It is also interesting that some of the communities living in fragmented, isolated forest patches adjacent to Budongo (some 25 km from the main block) are thought to use sticks during foraging (McLennan, 2011b;Reynolds, 2005;J. Wallis, personal communication, 2010).…”
Section: Tool Use Presence In Relation To Ugandan Forests' Evolutionamentioning
confidence: 99%
“…Although these results still demand further confirmation, they currently suggest that stick use is absent throughout Budongo Forest. It is also interesting that some of the communities living in fragmented, isolated forest patches adjacent to Budongo (some 25 km from the main block) are thought to use sticks during foraging (McLennan, 2011b;Reynolds, 2005;J. Wallis, personal communication, 2010).…”
Section: Tool Use Presence In Relation To Ugandan Forests' Evolutionamentioning
confidence: 99%
“…Chimpanzees in northern Uganda, for example, especially Budongo, have a smaller tool repertoire and use few or no stick tools [McLennan, 2014]. We can now document a number of possible large-scale patterns or "behavioural realms": the use of clubs to pound open beehives in Central African chimpanzees [Fay and Carroll, 1994;Hicks, 2004;Hicks et al, 2005;Boesch et al, 2009;Sanz and Morgan, 2009], honey-digging as primarily a central and eastern chimpanzee behaviour [Hicks et al, 2005;McLennan, 2011;Estienne et al, 2017a, b; but see Boesch and Boesch, 1990, for an example in West Africa], termite nest perforation in Central Africa [Sanz and Morgan, 2007] and nut-cracking in western chimpanzees [Boesch et al, 1994;Boesch and Boesch-Achermann, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent long-term sites have added entire new tool types to the species' repertoire, such as complex tool sets (Goualougo, Republic of Congo [Sanz and Morgan, 2007]; Loango, Gabon [Boesch et al, 2009]) and spears used to skewer bushbabies (Galago senegalensis) (Fongoli, Senegal [Pruetz and Bertolani, 2007]). New study sites have also expanded the range of previously discovered behaviours by hundreds of kilometres (honey-pounding at Loango [Boesch et al, 2009]; honey-digging at Bulindi, Uganda [McLennan, 2011]). Other shorter-term studies have revealed new behaviours ranging from brush-tipped fluid probes to "stepping sticks" and "seat sticks" (Tenkere, Sierra Leone [Alp, 1997]).…”
Section: Introductionmentioning
confidence: 99%
“…(see Figure 1). Bulindi chimpanzees use tools to excavate subterranean bee nests for honey-a behavior not recorded at Sonso or elsewhere in western Uganda 12 . The occurrence of GHC at Bulindi provides further evidence of behavioral variation among chimpanzees in the Budongo region.…”
Section: Discussionmentioning
confidence: 99%